Sexually transmitted infections in women who have sex with women. Issue 3 (28th May 2004) - Bailey, J V; Farquhar, C; Owen, C; Mangtani, P
Abstract : Objectives: To describe the prevalence of sexually transmitted infection (STIs) in a sample of women who have sex with women (WSW) and to identify risk factors for the acquisition of STI. Method: Cross sectional survey. Questionnaire for demographic, sexual history, and sexual practice data linked with the results of genitourinary examination. 708 new patients attending two sexual health clinics for lesbians and bisexual women in London were surveyed. Results: A majority of WSW reported sexual histories with men (82%). Bacterial vaginosis and candida species were commonly diagnosed (31.4% and 18.4% respectively). Genital warts, genital herpes, and trichomoniasis were infrequently diagnosed (1.6%, 1.1%, and 1.3% respectively). Chlamydia, pelvic inflammatory disease, and gonorrhoea infections were rare (0.6%, 0.3%, and 0.3% respectively) and diagnosed only in women who had histories of sex with men. Conclusions: Although we have demonstrated a low prevalence of STI, WSW may have sexual histories with men as well as women or histories of injecting drug use, and are therefore vulnerable to sexually transmitted or blood borne infections. Diagnosis of trichomoniasis, genital herpes, and genital warts in three women who had no history of sex with men implies that sexual transmission between women is possible.